Comparison of the Effect of Bleaching with 15% Carbamide Peroxide on the Flexural Strength of Three Resin-Based Restorative Materials - Soodabeh Kimyai; Yasaman Ghavami Lahij; Mehdi Daneshpooy; Elmira Jafari Navimipour; Parnian Alizadeh Oskoee (Tehran University of Medical Sciences, 2020)
Objectives: Considering the ever-increase use of vital bleaching procedures and an increase in the use of newly introduced resin-based materials for the restoration of teeth, this in vitro study was designed to evaluate the effect of 15% carbamide gel on the flexural strength of three resin-based restorative materials. Materials and Methods: Three different types of restorative materials, Beautifil II giomer, Cention N and Z250 micro-hybrid composite resin, were evaluated in the current study. Twenty-four bar-shaped samples were prepared from each restorative material, totaling 72 samples, and randomly assigned to two groups: with and without bleaching procedures (n=12). In the groups with a bleaching procedure, 15% carbamide peroxide gel was applied 8 hours a day for 14 days. The flexural strengths of the samples were determined. Two-way ANOVA and post hoc Tukey test were applied to compare the flexural strengths of the samples. Results: There were significant differences in the flexural strengths of the materials in terms of the exposure to the bleaching agent (P<0.05), with significantly higher flexural strength in the groups without a bleaching procedure. However, the mean flexural strengths were not significantly different in terms of the restorative material (P=0.12). Conclusion: It was concluded that 15% carbamide peroxide bleaching gel significantly decreased the flexural strengths of Beautifil II giomer, Cention N and Z250 micro-hybrid composite resin. There were no significant differences in the mean flexural strengths between the three resin-based restorative materials, irrespective of the use or no use of 15% carbamide peroxide gel.